Rancangan Alat Khusus Pelepas Front Accessory Support Engine Jt8d-15 di Program Studi Teknik Pesawat Udara - Ngakan Suara Apkara, Dewa; Esti Riyanti, Lilis (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
The JT8D-15 Engine is a turbofan-type gas turbine engine as a medium practice for cadets in conducting checks and maintenance. Due to the absence of front accessory support device for JT8D -15 engines in Hangar 01 Air aircraft Engineering study Program the author made a front accessory support release tool for JT8D -15 engines. An overview of removing front accessory support on JT8D -15 engines with the withdrawal method utilizes the load applied by the sled hammer. The first is to ensure that the design of the tool is able to be used in front accessory support engine JT8D -15, followed by the appropriate material selection in the design. The third stage was performed selection of cylinder screw and hammer muzzle shaft. Thus obtained the desired design dimension. And lastly, ensure that welding joints can withstand the voltage of the scissors that occur on a specific tool design. The results of this design are expected to assist in the implementation of Taruna practice on Gasturbine engine practice when releasing front accessory support engine JT8D -15. From the design achieved a strong design and can remove front accessory support engine JT8D -15.